Online support seeking, co-rumination, and mental health in adolescent girls - Mackenzie, Erin; McMaugh, Anne; Van Bergen, Penny; Parada, Roberto H. (Frontiers in Psychiatry, 2023)
Adolescents frequently use informal support seeking to cope with stress and worries. Past research in face-to-face contexts has shown that the relationship between informal support seeking and mental health is influenced by the specific strategy used and the mode through which support is sought. To date, little research has considered the relationship between support seeking online and adolescent mental health. In this study, structural equation modeling (SEM) examined the mediating role of co-rumination in the relationships between seeking support from friends or online and two measures of mental health: depression and anxiety. Participants were 186 adolescent girls, drawn from four independent girls’ schools in Sydney, Australia. Four brief vignettes described common social stressors and participants rated their likelihood of seeking support from close friends and from informal online sources. Co-rumination was measured using a short form of the Co-rumination Questionnaire and depression and anxiety were measured with the youth version of the Depression, Anxiety, and Stress Scale (DASS-Y). Different patterns of findings were found for support seeking from close friends and support seeking online. First, support seeking from friends was related to lower levels of depression and anxiety while seeking support online was related to higher levels depression and anxiety. Second, co-rumination suppressed the relationship between seeking support from friends and depression, but not online support seeking and depression or anxiety. These findings suggest that co-rumination reduces the benefits of seeking support from friends but is unrelated to online support seeking. The findings also confirm the problematic nature of online support seeking for adolescent girls’ mental health, particularly in response to social stressors.